Accelerating Materials Discovery Based on Generalized Low-dimensional Conformation Performance Relationships. Issue 1 (January 2020) - Qu, Yuanyuan; Meng, Xiangying; Jia, Zixi; Liu, Xiaofeng; Liu, Dongyan; Li, Shanshan; Bian, Fang
Abstract: The construction of conformation-performance relationships (CPRs) is the core issue of efficient material design. Different from traditional CPRs originating from experience summarizations or rational model cognitions, a strategy of generalized low-dimensional conformation-performance relationships (GLD-CPRs) for rapid material discovery has been established in this work by the aid of material information technology, providing us with a new perspective to material gene (MG) and its function on performance. From a pure computing perspective, the strategy has been concreted by a case study of semiconductor bandgap engineering. Based on more than 20, 000 items of self-produced semiconductor bandgap and attributes data, a set of CPRs for bandgap regulation towards arbitrary semiconductor of the same kind has be generated using GLD-CPRs strategy. By comparing with the reported studies, the reliability of the strategy is confirmed. Finally, future improvements needed by GLD-CPRs are addressed.